APFORGEN secures $1.48M to protect vital asian tree species - Jalonen, Riina; Yongqi, Zheng; Warrier, Rekha R. (2024)
The member countries of Asia-Pacific Forest Genetic Resources Programme (APFORGEN) jointly developed regional strategy that outlines the Programme’s contributions to the Global Plan of Action for the Conservation, Sustainable Use and Development of Forest Genetic Resources (United Nations Food and Agriculture Organization-FAO), and the Kunming-Montreal Global Biodiversity Framework. The Asia-Pacific Forestry Commission endorsed the strategy, which led to funding commitments from China, Germany, Republic of Korea, United Kingdom, and private sector partners for regional conservation, restoration, and capacity development.